Key determinants for growth in high-growth Ecuadorian manufacturing firms - Simbaña-Taipe, Luis (2019)
High-growth firms (HGFs) have awakened the interest of policymakers, especially on their contribution to increasing employment index. The aim of this research is to determine the key factors that influence the development of high-growth manufacturing companies in Ecuador. The research evaluated a sample of 143 HGFs between 2010 and 2015; the methodology of panel quantile regression was applied. The findings show that leverage, profitability, innovation, liquidity, solvency, and size have a positive impact on the growth rate of HGFs. Meanwhile, the age variable has a negative relationship in the equation. The results of this study provide solid elements to discuss and promote public and business policies in developing countries.